The daily economist : a chronicle of contemporary subjects showing the scope and originality of economic research and its application to real-world issues - Johnson, Harry G.; Weisbrod, Burton A. (Englewood Cliffs, N.J. : Prentice-Hall, 1973)
A chronicle of contemporary subjects showing the scope and originality of economic research and its application to real-world issues.
Includes bibliographical references: p. 231.
ijb, 18/01/2019
Loans
Keywords: Economics